PENGEMBANGAN MODUL PRAKTIKUM BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PENDIDIKAN FISIKA DI UNIVERSITAS ADZKIA - Ena Suma Indrawati; Lelfita; Novriandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Basic Physics learning in higher education requires a balanced mastery of conceptual understanding and science process skills. However, laboratory activities are often conducted in a procedural manner and do not sufficiently encourage students to think critically or engage in problem solving. This study aimed to develop a Problem Based Learning (PBL)–based laboratory module that is valid, practical, and effective in improving the learning outcomes of Physics Education students at Universitas Adzkia. The study employed an educational design research approach using the Plomp development model, which consists of the preliminary research, development, and assessment phases. The research participants were Physics Education students enrolled in the Basic Physics course. Research instruments included expert validation sheets, practicality questionnaires, and learning outcome tests. The results showed that the PBL-based laboratory module was categorized as highly valid, highly practical, and effective in improving students’ learning outcomes based on pretest and posttest results. Therefore, the PBL-based laboratory module is suitable for use as a learning resource to support more meaningful and problem-oriented Basic Physics laboratory activities.